The Effect of Basic Life Support Health Education on Increasing Knowledge and Skills in Cardiac Arrest - Rahmania Ambarika; Novita Ana Anggraini; Ans Syafrie Amroyan (Universitas STRADA Indonesia, 2024)
Background: Cardiac arrest is an emergency in which blood circulation suddenly stops, characterized by loss of arterial blood pressure. Cardiac arrest can be sudden and cause death. Cardiac arrest is a cause of high mortality. High mortality in Cardiac Arrest cases is due to slow help due to lack of knowledge and skills regarding Basic life Support. Purpose: The purpose of this study was to analyze the effect of Basic Life Support Health Education on increasing knowledge and skills in cardiac arrest in students. Method: This research design is Pra experimental with one group pre-post test conducted on 41 samples with simple random sampling. The instrument of thr research are used questionare for knowledge and observed for measured of the skil. Results:The results before being given health education the level of knowledge was less than 80.5% and the level of skills was less than 85.4%, while after being given health education the level of knowledge was good 53.7% and the level of skills was good 53.7%. From the analysis using the Wilcoxon Sign Rank Test, the p-value is 0.000 <0.05, there is an effect of increasing knowledge and skills before and after Basic Life Support health education for students. Conclusion: Health education with a short period of time can improve knowledge and skills but to improve high quality, training is needed for a long period.